2009
DOI: 10.1897/ieam_2008-069.1
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary life cycle metrics and tools for green buildings

Abstract: Building sector stakeholders need compelling metrics, tools, data, and case studies to support major investments in sustainable technologies. Proponents of green building widely claim that buildings integrating sustainable technologies are cost effective, but often these claims are based on incomplete, anecdotal evidence that is difficult to reproduce and defend. The claims suffer from 2 main weaknesses: 1) buildings on which claims are based are not necessarily "green" in a science-based, life cycle assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Additionally, although LCA is a widely used methodology to assess the environmental impact of buildings (Allacker et al 2011;Asif et al 2007;Feist et al 2001), the main focus of LCA studies of buildings has been on energy-related impacts (Passivhaus Institut 2006;Helgeson and Lippiatt 2009;Nemry et al 2010;Valderrama et al 2012;Zabalza Bribián et al 2009). Even in more comprehensive LCA-based evaluations, land use is not included.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although LCA is a widely used methodology to assess the environmental impact of buildings (Allacker et al 2011;Asif et al 2007;Feist et al 2001), the main focus of LCA studies of buildings has been on energy-related impacts (Passivhaus Institut 2006;Helgeson and Lippiatt 2009;Nemry et al 2010;Valderrama et al 2012;Zabalza Bribián et al 2009). Even in more comprehensive LCA-based evaluations, land use is not included.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, natural ventilation for the buildings is viable in the mid-seasons. The hybrid ventilation system is a feasible, low energy approach for building design, even in sub-tropical climates [30]. Khaleghi et al [31] concluded that, in general, mechanical ventilation can provide better indoor airquality, but the noise is an issue if the system is not properly designed.…”
Section: Challenges Of Indoor Air Quality and Ventilation Of Green Bumentioning
confidence: 99%
“…Almost a decade ago, the Applied Economics Office (AEO) at the National Institute of Standards and Technology (NIST) first proposed an approach to systematically assess the "returns" on sustainable building design that considers simultaneously: 1. environmental performance through life-cycle assessment (LCA) and 2. economic performance through life cycle costing (LCC) (Helgeson and Lippiatt 2009). Since this time, NIST has built a Net-Zero Energy Residential Test Facility (NZERTF) and systematically modeled LCC and LCA valuation verified through measured experimental data from the NZERTF (Healy, Kneifel, andWebb 2016…”
Section: List Ofmentioning
confidence: 99%